The Study of Web Page Design Improvement for "Selectedgoods" Company (Journal of Innovation, Business and Entrepreneurship, 2020)
In the fashion industry, there are smaller sector that are growing in the past ten years which is rugged menswear industry. Having experience as being in the industry, the founder of Selectedgoods felt there are gap between the leading brands and the small brands in the industry. Due to this gap occurring in the industry and established to help and aid the small brands to be able to compete with the leading brands in the industry. Based on this study, it shows that the root cause of Selectedgoods are poor performance of their internal team and have not done market test which makes the company does not understand the customer preference. Without having knowledge in developing a website, it is possible for Selectedgoods to create a platform with a substandard system and design, which might affect user experience. Therefore, this research is done to determine and plan the website interface design according to the customer preferences to improve customer satisfaction and experience towards the website. Based on the data collected, it shows that the consumers prefer the website to be personalized to its brand, a clean-looking layout, and like interactive features such as forum, weekly articles, and a chat feature.Keywords: E-Commerce, Rugged Menswear, Selectedgoods, Web Page Design